Ancestor’s Legacy: Response of Using People to Sacred Values and Social Function of Seblang Ritual - Saputra, Heru S. P. (UI Scholars Hub, 2014)
This article discusses the response of Using people to sacred values and social function of Seblang ritual in the context of Using society’s social structure in Banyuwangi, East Java. Library study, participatory observation, and in-depth interview are methods used in this research, while the analysis uses functional-structural method. The result of this study shows that the Seblang ritual is a social institution functioned by Using people as an integral part of their social structure. The sacredness of Seblang also become a meeting point between “alam alus” and “alam kasar”; between the spirits of village’s ancestors (dhanyang) and human beings; between macro cosmos and micro cosmos. The existence of the Seblang ritual’s institution crosses over the temporal boundaries, so until now Using people still maintain the practice as their social and cultural condition support its preservation. The cultural condition relates to religious and knowledge system, while the social condition relates to social structure and geographical environment of village. Such cultural and social conditions become the belief of Using people toward socio-cultural function of Seblang, particularly for fertility in agriculture and their welfare. “The outer power”, both state’s authority and political parties, cannot intervene the Seblang ritual. Implicit memory and meta-cognition constructed in the minds of the public have contributed to their belief in the value of sacred Seblang ritual. They believe the negation of ancestor’s legacy will cause disharmony, both socially and psychologically, which will also lead to disharmony in the social structure of Using society.